Phytoplankton functional group classifications as a tool for biomonitoring shallow lakes: a case study - Allende, Luz (2019)
We assessed changes in phytoplankton community structure in relation to environmental variables in an urban eutrophic shallow lake (Lake Lugano, Argentina) throughout one year following two classification systems according to the morpho-functional groups (MFG) approach and morphologically based functional groups (MBFG). We aimed to compare the different approaches and find a simple tool to biomonitor urban freshwaters regarding their phytoplankton structure. Values of transparency, nutrients and chlorophyll a concentrations confirmed the eutrophic/hypertrophic conditions of the lake. The potentially toxic Cyanobacteria Planktothrix agardhii representing MFG 5a and MBFG III was generally dominant and reached bloom densities (>62,000 ind ml 1 ). The multivariate analyses performed showed similar and overlapping results considering both approaches. Nutrients and transparency were the main environmental variables explaining the variance encountered. We conclude that MBFG classification was an adequate, easy-to-handle method for monitoring Lake Lugano. The functional approaches applied enabled the followup of potentially toxic Cyanobacteria in Lake Lugano. Further studies should include the estimation of cyanobacteria-derived toxin concentrations in water. We consider that the applicability of the MBFG approach deserves to be further explored as a promising tool for biomonitoring different types of urban water bodies.